The diversification of national football teams: Using the idea of migration corridors to explore the underlying structures of nationality changes amongst foreign-born players at the football World Cup - van Campenhout, G.; van Sterkenburg, J. (International Review for the Sociology of Sport, 2021)
The inclusion of foreign-born sportspeople in national sports teams has become increasingly common. At the same time, the assumed increase in diversity within national football teams has turned into a major subject of (inter)national controversy and debate. This applies, in particular, to the football World Cup, as the assumed increase in foreign-born players in national football teams detracts from the (homogeneous) nation-state basis of the Fédération Internationale de Football Association`s (FIFA) international football competitions. However, the actual dynamics and complexities of the presence of foreign-born players in national football teams within this context have remained under-researched. In this paper, we use the idea of `migration corridors` to examine the underlying structures that contribute to the diversification of national football teams, in particular during the World Cup. We do so from both an immigration and emigration perspective. By connecting our foreign-born player data to three types of migration corridors, we discuss the bidirectionality of player movements and nationality choices. Our outcomes indicate that the selection of foreign-born footballers within national football teams in the World Cup can mainly be considered as an echo and/or reversal of preceding migration flows between pairs of countries, indicating that historically embedded migration corridors sustain or are rediscovered in this process.